Endothelin‐1 Immunoreactivity and its Association with Intramedullary Hemorrhage and Myelomalacia in Naturally Occurring Disk Extrusion in Dogs. (29th June 2016) - Mayer, D.; Oevermann, A.; Seuberlich, T.; Vandevelde, M.; Casanova‐Nakayama, A.; Selimovic‐Hamza, S.; Forterre, F.; Henke, D.
Abstract : Background: The pathophysiology of ascending/descending myelomalacia (ADMM) after canine intervertebral disk (IVD) extrusion remains poorly understood. Vasoactive molecules might contribute. Hypothesis/Objectives: To investigate the immunoreactivity of endothelin‐1 (ET‐1) in the uninjured and injured spinal cord of dogs and its potential association with intramedullary hemorrhage and extension of myelomalacia. Animals: Eleven normal control and 34 dogs with thoracolumbar IVD extrusion. Methods: Spinal cord tissue of dogs retrospectively selected from our histopathologic database was examined histologically at the level of the extrusion (center) and in segments remote from the center. Endothelin‐1 immunoreactivity was examined immunohistochemically and by in situ hybridization. Associations between the immunoreactivity for ET‐1 and the severity of intramedullary hemorrhage or the extension of myelomalacia were examined. Results: Endothelin‐1 was expressed by astrocytes, macrophages, and neurons and only rarely by endothelial cells in all dogs. At the center, ET‐1 immunoreactivity was significantly higher in astrocytes (median score 4.02) and lower in neurons (3.21) than in control dogs (3.0 and 4.54) ( P < .001; P = .004) irrespective of the grade of hemorrhage or myelomalacia. In both astrocytes and neurons, there was a higher ET‐1 immunoreactivity in spinal cord regions remote from the center (4.58 and 4.15) than in the center itself ( P = .013; P = .001). ET‐1 mRNA was present in nearly all neurons with variable intensity, but not in astrocytes. Conclusion and Clinical Importance: Enhanced ET‐1 immunoreactivity over multiple spinal cord segments after IVD extrusion might play a role in the pathogenesis of ADMM. More effective quantitative techniques are required.